Development of Android-Based Game Media in Improving Students' Mathematical Literacy - Suryani, Eka; Susanti, Ely; Aisyah, Nyimas (Universitas Muhammadiyah Mataram, 2025)
This research aims to develop an Android-based learning media to enhance junior high school students' mathematical literacy, particularly in understanding numbers. It employs a development research approach with a qualitative methodology supported by quantitative data. The research follows the Research and Development (R&D) method, adapted from the Plomp model. The innovation involves the creation of a game-based learning media using an Android platform. The game itself is a web-based application developed through Wordwall. The study's subjects consist of 26 seventh-grade students, selected from MTs GUPPI Sukamoro in Banyuasin Regency and Srijaya Negara Junior High School in Palembang City. The data collection techniques used in this study included: (1) a validation sheet to assess the validity of the game product, (2) a student response questionnaire consisting of 11 questions to assess the practicality of the game, (3) pretest and posttest to assess students' mathematical literacy, and (4) interviews conducted if issues arose after the game and test were administered. Data analysis was carried out using quantitative methods. The validity and practicality levels of the data are analyzed using percentages, while the test data is evaluated based on the N-gain value. The results indicated that the Android-based game achieved a validity score of 77.54%, categorized as good. The data test results were 0.65 and 0.58, falling within the moderate criteria. Additionally, the classical average scores were 96.1% and 100%, with students achieving an average score of 84.69 and 83.88. These findings demonstrate that the Android-based learning media is both valid and effective in enhancing mathematical literacy on number concepts among seventh-grade students.